Highly Selective and Modular Synthesis of 3‐Aryl‐4‐(arylethynyl)‐2H‐chromen‐2‐ones from 2‐Iodoaryl 2‐Arylacetates through a Carbonylative Sonogashira Coupling–Intramolecular Aldol Cascade Reaction. Issue 23 (25th July 2016) - Chandrasekhar, Attoor; Ramkumar, Venkatachalam; Sankararaman, Sethuraman
Abstract : A modular method for the synthesis of 3‐aryl‐4‐(arylethynyl)‐2 H ‐chromen‐2‐ones from 2‐iodoaryl 2‐arylacetates and arylacetylenes has been developed. The carbonylative Sonogashira coupling–intramolecular aldol casade reaction was carried out in the presence of Pd(PPh3 )2 (Cl)2 as the catalyst. The one‐pot approach that involves the in situ formation of the 2‐iodoaryl 2‐arylacetates from the corresponding 2‐iodophenols and 2‐arylacetyl chlorides followed by the palladium‐catalyzed carbonylative annulation in the presence of the arylacetylene has also been described for the formation of the 3‐aryl‐4‐(arylethynyl)‐2 H ‐chromen‐2‐ones. Abstract : A modular approach for the synthesis of 3‐aryl‐4‐(arylethynyl)‐2 H ‐chromen‐2‐ones from iodoaryl 2‐arylacetates and arylacetylenes has been developed. This highly selective general method was used to prepare 24 different 3, 4‐disubstitued 2 H ‐chromen‐2‐one derivatives in good to excellent yields.